COVID-19: Coronavirus Vaccine Development Updates - Zhao, Jing; Zhao, Shan; Ou, Junxian; Zhang, Jing; Lan, Wendong; Guan, Wenyi; Wu, Xiaowei; Yan, Yuqian; Zhao, Wei; Wu, Jianguo; Chodosh, James; Zhang, Qiwei (Frontiers in Immunology, 2020)
Coronavirus Disease 2019 (COVID-19) is caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), a newly emerged coronavirus, and has been pandemic since March 2020 and led to many fatalities. Vaccines represent the most efficient means to control and stop the pandemic of COVID-19. However, currently there is no effective COVID-19 vaccine approved to use worldwide except for two human adenovirus vector vaccines, three inactivated vaccines, and one peptide vaccine for early or limited use in China and Russia. Safe and effective vaccines against COVID-19 are in urgent need. Researchers around the world are developing 213 COVID-19 candidate vaccines, among which 44 are in human trials. In this review, we summarize and analyze vaccine progress against SARS-CoV, Middle-East respiratory syndrome Coronavirus (MERS-CoV), and SARS-CoV-2, including inactivated vaccines, live attenuated vaccines, subunit vaccines, virus like particles, nucleic acid vaccines, and viral vector vaccines. As SARS-CoV-2, SARS-CoV, and MERS-CoV share the common genus, Betacoronavirus, this review of the major research progress will provide a reference and new insights into the COVID-19 vaccine design and development.